2018
DOI: 10.1002/hep.30156
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Sequencing Identifies a Serum MicroRNA Panel, Which Combined With Aspartate Aminotransferase to Platelet Ratio Index Can Detect and Monitor Liver Disease in Pediatric Cystic Fibrosis

Abstract: Cystic fibrosis (CF)-associated liver disease (CFLD) is a hepatobiliary complication of CF. Current diagnostic modalities rely on nonspecific assessments, whereas liver biopsy is the gold standard to assess severity of fibrosis. MicroRNAs (miRNAs) regulate liver disease pathogenesis and are proposed as diagnostic biomarkers. We investigated the combined use of serum miRNAs and aspartate aminotransferase (AST) to platelet ratio (APRI) to diagnose and assess CFLD severity. This was a cross-sectional cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…In recent years, researchers have focused on the role of miRNAs in the pathophysiology of hepatic fibrosis to determine its role in the regulation of HSC proliferation and differentiation 17 . Aberrant expression of several miRNAs was identified between resting and activated HSCs 18 . A recent study shows that miR-455-3p served as oncogene or anti-oncogene in different types of tumors 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have focused on the role of miRNAs in the pathophysiology of hepatic fibrosis to determine its role in the regulation of HSC proliferation and differentiation 17 . Aberrant expression of several miRNAs was identified between resting and activated HSCs 18 . A recent study shows that miR-455-3p served as oncogene or anti-oncogene in different types of tumors 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Figure 1D) or CFLD (r=-0.1, p=0.6, not shown). We previously demonstrated the use of APRI for detection of liver disease and in staging fibrosis severity in pediatric CFLD 15,20 . In the current cohort, contemporaneous blood test results were available for calculation of APRI in 72/105 subjects with CFnoLD and 23/33 with CFLD.…”
Section: Influence Of Age On Liver Stiffnessmentioning
confidence: 99%
“…Different non-invasive assessment tools have been assessed to improve diagnostic accuracy for both liver disease detection in pediatric CF and hepatic fibrosis staging in CFLD including APRI, Fibrosis-4 (FIB-4) and serum microRNAs 15,20 . In this study, by combining LSM and APRI in a CART recursive partition model, the AUROC for detecting CFLD improved to 0.89, and predicted 18.6-times greater odds of children with CF having CFLD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(D) Scatterplot illustrates cut-points determined by CART modelling used to discriminate CFLD from CFnoLD children. Blue dots represent CFnoLD.Red dots represent CFLDSeveral studies have shown the use of APRI as a non-invasive biomarker for the detection of CFLD(124,232). ROC curve analysis of APRI for detection of liver disease in this cohort (i.e., CFLD vs CFnoLD) showed an AUC= 0.74 (P=0.0040), similar to previous reports(124).…”
supporting
confidence: 85%